EVALUASI PENGGUNAAN TEKNOLOGI MEDIA SOSIAL DALAM MEMPERLUAS BISNIS PEMASARAN ONLINE - Sandy Kosasi (CCIT Journal, 2017)
This research aimed to evaluate the use of information technology governance in expanding online marketing businesses. Cosmetics were researched products. AI (Acquire and Implement) and ME (Monitor and Evaluate) under COBIT 4.1 Framework were concerned. Respondents working in 35 companies and using social media technology for online marketing businesses were surveyed. This research also aimed to find out the gap values of the use of social media technology of online marketing businesses based on AI and ME Domains. Implications on managerial aspects and information technology governance show that there are relationships among information technology processes of AI, ME, and others. Research results show that the highest gap values (0.544 and 0.465) are at AI4 and ME4 Processes. These values are also at the lowest maturity levels (2.456 and 2.535). Moreover, AI4 is related to input control objectives (PO10, AI1, AI2, AI3, AI7, and DS7) and output control objectives (AI7, DS4, DS8, DS9, DS11, DS13, and DS7). On the other hand, ME4 is related to input control objectives (PO4, PO5, PO9, ME2, and ME3) and output control objectives (PO4, PO1, ME1, PO5, PO1, and PO9).